Theological librarians and the internet implications for practice - Stover, Mark (Birmingham, NY Haworth Information, 2001)
Includes bibliographical references andmindex.
Co-published simultaneously as Journal of Religious and Theological Infomation, Vol. 3, Nos 3/4, 2001
Keywords: Theological libraries; Library information networks; Theology -- computer network resources